Analysis of the Impact of Excessive TikTok Use on Students Across All Faculties at Universitas Negeri Medan - Monika Choirala Purba (PT. Global Research Collaboration, 2025)
Advances in digital technology have intensified social media engagement among university students, with TikTok emerging as one of the most frequently used short-video platforms and raising concerns about its academic and psychosocial implications. This study aimed to analyze the perceived impact of excessive TikTok use among students across all faculties at Universitas Negeri Medan. A quantitative cross-sectional survey was conducted using a 15-item Likert-scale questionnaire. A total of 72 respondents were recruited through accidental sampling, and data were collected online via Google Forms from November 26 to December 2, 2025. Descriptive statistics (frequencies, percentages, and mean scores) were applied to summarize responses and categorize the overall impact level. The findings indicate that the perceived impact of TikTok use falls within the high category, suggesting that students commonly recognize the influence of excessive use on learning focus, time management, face-to-face social interaction, and academic behavior. Despite these risks, respondents also acknowledged TikTok’s constructive potential when used purposefully, particularly as a medium for accessing educational content and supporting creativity. These results imply that institutional and individual strategies should focus on strengthening digital literacy and self-regulation to mitigate negative outcomes while optimizing educational benefits. In conclusion, excessive TikTok use is perceived to have substantial academic and social consequences among students, yet targeted guidance and responsible use can transform the platform into a productive learning resource.